Higher-order modeling of anisogrid composite lattice structures with complex geometries. (1st October 2021) - Tornabene, Francesco; Viscoti, Matteo; Dimitri, Rossana; Antonietta Aiello, Maria
Highlights: Mode frequencies and shapes of curved lattice structures have been investigated, employing the GDQ method. A generalized RVE homogenization has allowed to model different cell configurations. An Higher Order Equivalent Single Layer (ESL) approach has implemented. A very good agreement has been found with refined FEM models. Abstract: The work investigates the vibration behaviour of anisogrid composite lattice shell structures, typically formed by a system of geodesic unidirectional composite ribs. A homogenization approach is here embedded within an Equivalent Single Layer (ESL) formulation for doubly-curved shells, accounting for the geometric contribution of cell patterns. The lattice shells are modelled as anisotropic homogenized continuous structures characterized by effective stiffness parameters. The governing equations of motion are derived using the Higher-order Shear Deformation Theories (HSDTs) of shells, whereas the Generalized Differential Quadrature (GDQ) method is applied to determine the fundamental frequencies with a reduced computational effort. A piecewise field variable assumption is considered for a proper description of zigzag interfacial effects between the lattice core and the external skins. The reliability and efficiency of the proposed numerical strategy is verified by comparison with finite element-based predictions. A systematic analysis aims at studying the effect of different geometric and stiffness parameters, e.g. the number of ribs, their cross-sectional dimensions, orientation and spacing, on the magnitude of the fundamental frequencies for some lattice structural members that could be of great interest for design purposes in the aerospace or automotive engineering practice.